Restoring biodiversity in degraded secondary rain forest in Sabah, Malaysia - Waern, Sara (2015)
Many tropical rain forests has been lost or degraded as a result of human activities and environmental factors. Since the level of biodiversity is high in the tropics, maintaining these areas is of great importance. Forests like these are often assumed to benefit from forest restoration and rehabilitation. The INIKEA project area in Eastern Sabah, Malaysian Borneo, aims to improve biodiversity and/or species richness in the degraded forest through enrichment planting with indigenous species. The objective of this thesis was to evaluate how different treatments (liberation, gap-cluster planting and line planting) affect the biodiversity of natural regeneration in different forest types in the Rain forest Restoration Experiment, located in the INIKEA project area. The forest in this experiment was divided into three types based on the degree of disturbance they had been exposed to. Species richness, species rank abundance (including evenness), biodiversity indices and measurements of ecological distance were compared between treatments and forest types for all size classes of forest vegetation (i.e. trees, saplings, seedlings and seeds). The results showed that there were almost no differences regarding biodiversity in natural regeneration between treatments, but some significant differences between forest types. However, the differences between forest types were not consistent throughout all analyses. The differences between forest types may indicate that they are in need of different treatments when practicing restoration. Also, large differences in species richness and evenness could be observed between the different tree size classes. The greater differences between forest types than between treatments could be explained by the recently performed treatments. The forest types have been constant for a longer time period and the differences should be larger between the forest types than the treatments. The differences between the size classes could mostly be explained by inter- and intraspecific competition and the, at the time of the inventory, ongoing mast fruiting. To be able to observe possible differences between the effects of the treatments in this project, more time is needed.